81 Reproductive Dysfunction in Cattle Following Vaccination Not a Result of Viral Infection of the Reproductive Tract. (8th March 2022) - Epperson, Kaitlin M; Rich, Jerica J J; Northrop-Albrecht, Emmalee J; Beck, Erin; Perkins, Stephanie; Daly, Russell F; Perry, George A
Abstract: Impairment of bovine reproductive function and decreased pregnancy rates have been reported in modified-live vaccinated females. The objective of this study was to determine if virus could be found in various areas of the bovine reproductive tract following vaccination. Previously vaccinated beef females (n = 50) were administered a single dose of one of three treatments on d0 of the estrous cycle; BoviShield (n = 20), Titanium 5 (n = 20), or ViraShield (n = 10) based on estrus expression. Blood samples were collected on d0, 15, and 30 to evaluate Infectious Bovine-Rhinotracheitis (IBR) and Bovine Viral Diarrhea Virus (BVDV) titers and progesterone concentrations. On d15/16, half the animals from each treatment were non-surgically flushed with sterile saline (Uterine Fluid), and uterine biopsies (Uterine Tissue) were collected. On d17, follicular fluid and granulosa cells were collected by follicle aspirations. Remaining animals had uteri flushed and uterine tissue collected on d29, and follicles aspirated on d31. All samples were evaluated for presence of virus. Data were analyzed using the MIXED procedure of SAS. Sub-luteal progesterone concentrations were observed in 15% of the BoviShield and Titanium treatments on d15 and d30, versus 0% in the ViraShield treatment. Virus isolation and RT-PCR results were negative in all samples for all animals. Titers for BVDV-1 did not differ between treatments (P = 0.99) or treatment by time (P = 0.48). Titers for IBR tended to differ by treatment (P = 0.09) and treatment by time (P = 0.06), while BVDV-2 titers were affected by treatment (P < 0.01) and treatment x time (P < 0.01). Sub-luteal progesterone animals had a rapid rise in IBR and BVDV-2 titers from d0 to d15 and then tended (P < 0.07) to decrease to d30, compared to animals that had normal cycles where titers increased from d0 to d15 and remained elevated on d30. Collectively, these results indicate an alternative mechanism of impacting reproductive efficiency, possibly through an immune response.